Studies in islam 3 - Maulvi abdul aziz (Paramount book (PVT) LTD., 2000)
"Studies in Islam" by Maulvi Abdul Aziz is a scholarly work that explores various aspects of Islamic teachings, history, and philosophy, offering insights into the principles and practices of Islam.